2020
DOI: 10.3390/met10040497
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Titanium from Low-Grade Ore with Different Leaching Agents in Autoclave

Abstract: The progressive depletion of primary sources to obtain metals has led to the search for alternative sources for their recovery. In the particular case of titanium, titaniferous sands are a viable option for obtaining this metal. This paper presents the results of the dissolution of titanium from titaniferous sands of Buenos Aires province (Argentina) in a laboratory autoclave (450 mL of capacity). The operating parameters studied were as follows: different acids (HF, H2SO4 and mixtures of these acids); leachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Further ICP‐OES analysis was performed to quantify the amount of copper leached‐out (titanium leached‐out in highly acidic condition) [53] in the filtrate after the reaction. For this study, standard copper solutions at different concentrations from 0.1 to 10 ppm were prepared and analyzed in ICP‐OES, in which an emission wavelength of copper was observed at 327.395 nm (Figure 1c) and standard linear curve exhibited between the concentration and intensity (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Further ICP‐OES analysis was performed to quantify the amount of copper leached‐out (titanium leached‐out in highly acidic condition) [53] in the filtrate after the reaction. For this study, standard copper solutions at different concentrations from 0.1 to 10 ppm were prepared and analyzed in ICP‐OES, in which an emission wavelength of copper was observed at 327.395 nm (Figure 1c) and standard linear curve exhibited between the concentration and intensity (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Today, the fluoride processing method of ilmenite and rutile is very actively developing [23][24][25][26][27][28]. This method is very promising and has a very strong basis for the development of this technology, because it is economical, has a low amount of waste, and has the ability to recycle the main components [29][30][31][32][33][34][35][36][37]. For example, the authors of [29,30,37] worked with titanium dioxide, which is found in industrial waste or in low-grade materials.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested using the residues of sulfate leaching into cement. Rodriguez et al [33] show the leaching of titanium from lean ore by various leaching agents in an autoclave. The optimal process parameters were obtained to achieve 89% titanium recovery: leaching at 123 • C, 330 rpm, 80 min, and 1.8% w/v with a mixture of 15% HF and 10% H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, the development of the sulfate method associated with the introduction of various reagents (additives) sulfuric acid. For example, in [5] a water technology is described, in which it is recommended to use a mixture of H 2 SO 4 (10% vol. )-HF (15% vol.)…”
Section: Introductionmentioning
confidence: 99%